Evaluación participativa y herramientas digitales en escenarios de ayuda humanitaria / Participatory evaluation and digital tools in humanitarian aid settings - Ángel De-Juanas-Olivas; Francisco Javier García-Castilla; Jorge Díaz-Esterri; Diego Galán-Casado (Revista Latinoamericana de Tecnología Educativa)
Information gathering may obviously be a complex process during a humanitarian crisis for both relief workers and its victims. Faced with the inherent difficulties, digital tools have much to contribute to the different phases of participatory evaluation. This article presents partial results of the Erasmus+ project, KA2- Cooperation for innovation and the exchange of good practices (InovHumbRE Projects). The main aim has been to analyse data on the participatory evaluation methods used by the different institutions/agencies involved in a project and within the context of crisis situations. A mixed type of study was selected using a descriptive and interpretative approach of a non-generalisable nature based on an analysis of quantitative and qualitative data provided by the staff of non-governmental organisations working in crisis situations in Spain. The cohort was comprised of 14 respondents from sundry social agencies and organisations. A questionnaire was used with 26 items that followed an open-ended and closed response format. The results show that the use and development of technology can favour social interventions and participatory evaluations in certain projects or crisis situations.